2016
DOI: 10.1007/s11665-016-2294-y
|View full text |Cite|
|
Sign up to set email alerts
|

On the Influence of Material Parameters in a Complex Material Model for Powder Compaction

Abstract: Parameters in a complex material model for powder compaction, based on a continuum mechanics approach, are evaluated using real insert geometries. The parameter sensitivity with respect to density and stress after compaction, pertinent to a wide range of geometries, is studied in order to investigate completeness and limitations of the material model. Finite element simulations with varied material parameters are used to build surrogate models for the sensitivity study. The conclusion from this analysis is tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 14 publications
3
19
0
Order By: Relevance
“…Input from this research is important and useful for future efforts to accurately simulate the pressing behavior of the presently analyzed powders. Together with the results presented in previous research (Ref 6,[16][17][18], it is believed that future FE simulations will give relevant results for the press tool compensations mentioned above. Both FE simulations of powder compaction (Ref 5,19,20) as well as simulations using the discrete element method (DEM) (Ref [21][22][23][24] can in the future gain from the present results.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Input from this research is important and useful for future efforts to accurately simulate the pressing behavior of the presently analyzed powders. Together with the results presented in previous research (Ref 6,[16][17][18], it is believed that future FE simulations will give relevant results for the press tool compensations mentioned above. Both FE simulations of powder compaction (Ref 5,19,20) as well as simulations using the discrete element method (DEM) (Ref [21][22][23][24] can in the future gain from the present results.…”
Section: Introductionsupporting
confidence: 64%
“…Powder A and Powder B used in the experiments are spraydried WC-Co mixtures also used in previous research (Ref 7,[16][17][18]21). The average particle size for Powder A is smaller than Powder B, which typically leads to higher press forces to achieve a given relative material density.…”
Section: Test Setupmentioning
confidence: 99%
“…Previous research with an instrumented pressing tool, together with reverse engineering, gave useful but insufficient data for a complete set of material parameters [9]. A sensitivity study of the material model showed that the density after pressing is an important variable when defining the material parameters [10,11]. The present measurements are thus of high importance for characterization of the material used in the FE-simulations.…”
Section: Introductionmentioning
confidence: 89%
“…All samples are produced from the same cemented carbide powder raw material, which is a WC-Co mixture containing roughly 88 % WC, 10 % Co together with 2 % PEG (measured in weight). It is a spray-dried refractory carbide and a metal powder mixture of the same type as used in previous research [1,3,8,11,21]. The WC and Co particles have a representative size of approximately 1 μm, while the corresponding size for the granules, after spray-drying, is in the order of 100 μm.…”
Section: Test Specimensmentioning
confidence: 99%
See 1 more Smart Citation